Perception of biological motion in visual agnosia - Huberle, Elisabeth; Rupek, Paul; Lappe, Markus; Karnath, Hans-Otto (Frontiers in Behavioral Neuroscience, 2012)
Over the past twenty-five years, visual processing has been discussed in the context of the dual stream hypothesis consisting of a ventral (‘what') and a dorsal ('where') visual information processing pathway. Patients with brain damage of the ventral pathway typically present with signs of visual agnosia, the inability to identify and discriminate objects by visual exploration, but show normal perception of motion perception. A dissociation between the perception of biological motion and non-biological motion has been suggested: Perception of biological motion might be impaired when 'non-biological' motion perception is intact and vice versa. The impact of object recognition on the perception of biological motion remains unclear. We thus investigated this question in a patient with severe visual agnosia, who showed normal perception of non-biological motion. The data suggested that the patient's perception of biological motion remained largely intact. However, when tested with objects constructed of coherently moving dots (‘Shape-from-Motion’), recognition was severely impaired. The results are discussed in the context of possible mechanisms of biological motion perception.